A educação musical e seus fins - Banci, Vanderlei Aparecido (2021)
The present study focuses on music education for children in the basic education at municipal schools in Guarulhos. The investigation aims at demonstrating the music education offered in the schools, revealing, at one hand, the pretension and proposals of both the schools’ educators and the Education Secretary, and, on the hand, the proposal incorporated by the students. My hypothesis is that music education may transform the relation with the emotions and the feelings. The research was carried out through the investigation of the purposes of music education based on the development of the musical language in the aspects of singing, hearing, writing, creativity and signification. The theoretical and methodological references are supported by the works and analyses of L. S. Vigotski, mainly “The Psychology of Art”, and also of Adorno. The work constitutes empirical research, with interviews with two teachers, and also with two of their previous students which have experienced musical education. The teachers either have a degree in Music, or are licensed in music education. They are public servants of Guarulhos Municipal Education Secretary. The research also included bibliographic survey of the institutions and teachers’ documents. More specifically, I analyzed the following documents: Common National Curriculum Base (BNCC); Curriculum Proposal of the Municipal Network of Guarulhos (QSN); Political Pedagogical Projects (PPPs) of three Guarulhos Municipal Schools, where the interviewed teachers worked; Continued Education Program offered by the Education Secretary for music educators; three pedagogical plans of the interviewed teacher; and the interviews made with the four subjects. The results corroborate the initial hypothesis, evincing the relevance and necessity of music education in schools from early childhood to high school